Truman K. Gibson papers - Gibson, Truman K. (Truman Kella), 1912-2005.
Correspondence, memoranda, newspaper clippings, printed matter, photographs, and other papers reflecting the social life of the Gibson family in Chicago, Ill. Includes Gibson's correspondence with his wife, Isabelle Carson Gibson, written while he served as an advisor on African American affairs to the U.S. War Dept., in Washington, D.C., during World War II. Topics include discrimination and segregation in the military, political and civic events in which Gibson was a participant, and the International Boxing Club, an organization he helped found.
Lawyer, business executive, and boxing promoter.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Gibson, Isabelle Carson -- Correspondence; Gibson family; International Boxing Club; United States. -- War Department; African Americans -- Military service; African Americans -- Segregation; African Americans -- Illinois -- Chicago -- Social life and customs; Boxing; Racism; World War, 1939-1945 -- Participation, African American; World War, 1939-1945 -- Washington (D.C.); Executives; Lawyers; Sports promoters